Anger, Faith and Bewildered Fragments of Self: The Shaping of Ethos in an Argentinean Translation of Sarah Kane's 4.48 Psychosis - Spoturno, María Laura (2022)
4.48 Psychosis is British playwright Sarah Kane's final play. Its opening took place at the Royal Court Theatre Upstairs in London in June 2000, only a few months after Kane's suicide. The initial reception of the play was surrounded by controversy in the United Kingdom, with some reviewers and critics interpreting the theatrical text as primarily autobiographical. Informed by a socio-discursive perspective, which specifically looks at the construction of ethos, this paper aims at contributing to the study of subjectivity in translated drama. Focusing on Rafael Spregelburd's Argentinean Spanish translation of 4.48 Psychosis, published by Losada in 2006, we explore the shaping of subjectivity in the translated dramatic text highlighting the way in which the persona of the translator builds within and beyond the translated text. While Spregelburd's translation uses dramatic strategies and techniques that successfully foster the image or ethos of a rupturist playwright, it still stresses the autobiographical character often attributed to the text. This is particularly evident in the female gender construction of the main voice in the play, which is ambiguous in the source text. Assessed within the framework of Spregelburd's whole production, our analysis also explores the construction of the translator's persona and positioning in the target dramatic text and system.